Tosca - Puccini, Giacomo. 1858-1924
Tosca, Opera en 3 actos, Libretto: Victoreen Sardou, Luigí Illica y Giuseppe Giacosa, Metropolitan Opera Chorus, Orchestra, Director: Giuseppe Sinopoli, Production: Franco Zifferelli